The Analysis of Future Prospects in the Middle of the 19th Century in Lithuania - Genzelis, Bronislovas (Problemos, 1970)
Cruel social and national oppression forced Lithuanian thinkers to analyse future prospects of the country. They took an interest in the most suitable economic relations to Lithuania, in the fate of the Lithuanian nation. A great number of our thinkers of that period approved of the idea of founding the bourgeois type of the state. Opinions differed on the second question: some, e.g., P. Dalevskis, J. Geištoras, considering Lithuania annexed to Poland forever, denied both its political and cultural independence and looked upon Lithuania as a future province of Poland; others (M. Akelaitis, S. Sierakowski) maintained the view that the best way out is to merge neighbouring countries into a federal state, every state having its equal rights and absolute autonomy. The third group (E. J. Daukšys, K. Kalinauskas) strove to establish an independent state of Lithuania; the fourth group (L. Ivinskis, M. Valančius) did not solve the problem of Lithuania’s system, considering it a future problem, and tried their best to preserve the national originality of the Lithuanian.